Centre-Based Care and Parenting Activities - Jonas Jessen; Christa Katharina Spieß; Sevrin Waights (Oxford Bulletin of Economics and Statistics, 2022)
We examine the relationship between parenting activities and centre-based care using time diary and survey data for mothers in Germany. While mothers using centre-based care spend significantly less time in the presence of their child, we find that differences in the time spent on specific activities such as reading, talking, and playing with the child are relatively small or zero. The pattern of results is more pronounced for lower education mothers. The lack of large decreases in activities is explained by two factors: (i) that centre care replaces time that parents spend with the child but are doing other things such as housework or leisure (a small direct effect), and (ii) that evenings become relatively more activity-rich (a compensating indirect effect). For the intensive margin (full-day vs. half-day), we find more additional reductions in parenting activities, but these are compensated for by lower education mothers during non-centre hours. Our findings represent novel evidence that activities in the home environment are a complement to centre-based care, highlighting a credible additional mechanism for child development effects of centre-based care.
Keywords: 330